(untitled) (Academia Science Repository, 2023)
One of the main ideas of modern specialists in Pedagogical Sciences it is necessary to study new methods of conducting educational work, complete trends, optimal needs, cognitive needs of parents. Innovation in preschool education is characterized by methodological practices and the uniqueness of the form, which are sought everywhere on the experimental and creative understanding of established educational traditions, the problem of "pseudo-nuclear" is acute, characterized by the originality of the form. Therefore, it is difficult to ensure that even teachers with many years of practice carry out consistent innovations in the activities of experimental pedagogical sites and preschool organizations. This article provides feedback and insights into the use of innovative technologies in the preschool education system and the study of child psychoanalysis.